Fot. Kosycarz : niezwykłe zwykłe zdjęcia. Cz. 3 / [Zbigniew Kosycarz, Maciej Kosycarz ; red. i oprac. Maciej Kosycarz]. - Kosycarz, Zbigniew (1925-1995) (Kosycarz Foto Press/KFP, 2008)
Album fotografii.